Acquiring high expression of suilysin enable non-epidemic Streptococccus suis to cause streptococcal toxic shock-like syndrome (STSLS) through NLRP3 inflammasome hyperactivation. Issue 1 (1st January 2021) - Xu, Lei; Lin, Lan; Lu, Xi; Xiao, Peng; Liu, Ran; Wu, Meizhou; Jin, Meilin; Zhang, Anding
ABSTRACT: The epidemic Streptococcus suis ( S. suis ) strain [Sequence type (ST) 7] was gradually evolving from the non-epidemic ST1 strain and got the ability for high expressing of suilysin (SLY). And the high expression of SLY was required for the epidemic strain to cause NLRP3 hyperactivation, which is essential for the induction of cytokines storm, dysfunction of multiple organs, and a high incidence of mortality, the characters of streptococcal toxic shock-like syndrome (STSLS). However, it remains to be elucidated whether acquiring high SLY expression due to genome evolution was sufficient for the non-epidemic strain to cause STSLS. Here, we found that the overexpression of SLY in ST1 strain (P1/7-SLY) could obviously increase the inflammasome activation, which was dependent on NLRP3 signalling. In contrast, the strain (P1/7-mSLY) overexpressing the mutant SLY (protein without hemolytic activity) could not significantly increase the inflammasome activation. Furthermore, similar to the epidemic strain, P1/7-SLY could cause STSLS in nlrp3 +/+ mice but not in nlrp3 −/− mice. In contrast, P1/7-mSLY could not cause STSLS in both nlrp3 +/+ mice and nlrp3 −/− mice. In summary, we demonstrate that genetic evolution enabling S. suis strain to express high level of SLY may be an essential and sufficient condition for NLRP3 inflammasome hyperactivation, which could further cause cytokines storm and STSLS.